THE STRENGTH AND CONSISTENCY OF SELF COMPACTING CONCRETE BY RICE HUSK ASH AS ADDITIVE - Ahmad, Khalid Soliman; Kristiawan, Stefanus Adi; Asâad, Sholihin (Jurnal Teknik Sipil, 2014)
AbstractSelf-compacting concrete (SCC) is a flowing concrete mixture that is able to consolidate under its own weight. Many countries have the problem of shortage of conventional cementing materials. Recently there is  considerable  efforts  worldwide  by  utilizing indigenous and waste materials in concrete. One of  such  materials  is  the  rice  husk  which  under controlled burning. Rice Husk Ash (RHA), produced after the burning of Rice husks (RH) has high reactivity and pozzolanic property. The use of RHA in this experiment is expected to determine the effect of RHA on Self Compacting Concrete. The use of Rice Husk Ash of Self Compacting Concrete as a matrix cannot increase the compressive strength of the SCC. Highest value obtained at RHA 0% of 27.18 MPa and RHA 20% of 22.08 MPa. Silica (SiO2) content in RHA of 82.59% (due to uncompleted burning) showed insufficient standard value required to produce optimal CSH bond on concrete,  which is silica content of at least 85% to increase the strength of concrete. Temperature reaction increases due to the increasing of calcium oxide. This condition makes more calcium hydroxide released by cement when cement reacts with water. With the higher of calcium hydroxide so that the adhesion of cement will be reduced and makes the structure weaker and then cause a lower compressive strength. Keywords: SCC, fly ash, RHA, consistency, compressive strength